Room Temperature Regioselective Catalytic Hydrodefluorination of Fluoroarenes with trans‐[Ru(NHC)4H2] through a Concerted Nucleophilic Ru−H Attack Pathway. Issue 6 (9th January 2017) - Cybulski, Mateusz K.; McKay, David; Macgregor, Stuart A.; Mahon, Mary F.; Whittlesey, Michael K.
Abstract: The efficient and highly selective room temperature hydrodefluorination (HDF) of fluoroarenes by the trans‐[Ru(IMe4 )4 H2 ] catalyst, 3, is reported. Mechanistic studies show 3 acts directly in catalysis without any ligand dissociation and DFT calculations indicate a concerted nucleophilic attack mechanism. The calculations fully account for the observed selectivities which corroborate earlier predictions regarding the selectivity of HDF. Abstract : The reason for selectivity : Efficient and selective hydrodefluorination of fluoroarenes by a trans ‐[Ru(NHC)4 H2 ] catalyst is reported. DFT calculations indicate that the observed selectivities are fully consistent with a concerted nucleophilic attack mechanism without any prior ligand dissociation.